Revitalisasi Tradisi Nahunan dalam Praktik Asuhan Ibu dan Bayi Dayak Ngaju - Lensi Natalia Tambunan; Graciella Ayundha P; Karin Cin Melin; Monica Anggraini; Monika Monika; Naiya Naiya; Nabila Nabila; Nanda Liana; Nindie Kirana; Novita Belina (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
This study explores the meaning and role of the Nahunan tradition in maternal and infant care among the Dayak Ngaju community. A descriptive qualitative method was employed, utilizing literature review and field interviews. The findings reveal that Nahunan is not merely a naming ritual, but also symbolizes spiritual protection and social acceptance of the child. The practice involves traditional leaders, herbal remedies, and natural symbols. However, modern influences have diminished the younger generation’s understanding of its values. Preserving local culture within healthcare services is essential to maintaining community identity.